Werkverzeichnis Anton Bruckner, Band 1 : WAB 1 bis WAB 95 - Klugseder, Robert; Gubsch, Clemens; Mayer, Desiree (Hollitzer, 2024)
Based on the 149 works listed in Renate Grasberger's older catalogue of works, the new catalogue has been expanded to over 300 works, including autograph sketches, study materials, copies and arrangements. A novelty of the new catalogue of works is the inclusion of polyphonic music incipits, in the case of multi-part works also for the beginning of each section.